Controlled Growth of TiO2 Nanoparticles on Graphene by Hydrothermal Method for Visible-Light Photocatalysis - Thanh-Lieu T. Le; Thanh-Hiep T. Le; Nguyen Van Kim; Hao Van Bui; Le Truong Giang; Vo Vien (My University, 2021)
Controlled Growth of TiO2 Nanoparticles on Graphene by Hydrothermal Method for Visible-Light Photocatalysis
Keywords: TiO2/Graphene; Thủy nhiệt; Quang xúc tác khả kiến